Hearing and Heeding the Voices of those With Advanced Illnesses. Issue 4 (October 2020) - Piderman, Katherine M.; Radecki Breitkopf, Carmen; Jenkins, Sarah M.; Ingram, Cory; Sytsma, Terin T.; Lapid, Maria I.; Tata, Beba S.; Chatterjee, Krishanu; Egginton, Jason S.; Jatoi, Aminah
Objectives: To describe the feasibility of a chaplain-led spiritually focused life review interview and the development of a spiritual legacy document (SLD) for patients with advanced diseases and to describe changes in spiritual well-being (SWB), spiritual coping strategies (SC), and quality of life (QOL) after receiving the SLD. Patients and Methods: In all, 130 patients and support person (SP) pairs were recruited from July 2012 to January 2019. Following enrollment, demographic information was gathered and baseline questionnaires were administered. Functional Assessment of Chronic Illness Therapy–Spiritual Well-Being Scale (FACIT-Sp-12) and a linear analog scale assessment (LASA) measured SWB. LASAs also measured QOL and emotional well-being (EWB). Positive Religious Coping Scale (RCOPE) measured SC. After completion of baseline forms, participants were interviewed (individually) by a chaplain. Interviews were digitally recorded, transcribed, and verified. Transcripts were edited and participants were given the opportunity to make adaptations. The participant-approved draft was then developed into a professionally printed SLD. Follow-up questionnaires were administered to assess change. Results: Significant improvements from baseline to post-SLD follow-up were found for patients on the LASAs: SWB (average 7.7-8.3, P = .01), QOL (average 6.7-7.3, P = .03), EWB (average 6.9-7.5, P = .01), and on the positive RCOPE (average 1.8-2.0, P = .007). Effect sizes were approximately 0.25. Considering any improvement, 61.0% improved their positive RCOPE score, 46.6% improved EWB, and 39.7% improved SWB. No significant changes were found on the FACIT-Sp-12. No significant changes were found for SPs. Conclusion: The results suggest that the primary participants who completed the study benefited by significantly increasing their QOL, SWB, EWB, and SC.